Optical and transport properties of transparent conducting La-doped SrSnO3 thin films. (13th October 2015) - Baba, Erina; Kan, Daisuke; Yamada, Yasuhiro; Haruta, Mitsutaka; Kurata, Hiroki; Kanemitsu, Yoshihiko; Shimakawa, Yuichi
Abstract: We investigated optical and transport properties of transparent conducting La-doped strontium stannate epitaxial thin films prepared by pulsed laser deposition. The prepared films are transparent with no apparent optical absorptions in the wavelength range between 390 and 1600 nm. The room-temperature electrical resistivity decreases with increasing carrier concentration and reaches values as low as 1 mΩ cm. The mobility shows the maximum of 40 cm 2 (V s) −1 at a carrier concentration of about 9  ×  10 19 cm −3 . At that concentration the predominant transport mechanism of the films changes from scattering by lattice defects to scattering by ionized dopants.